NEW COMPARATIVE MYTHOLOGY: POSSIBILITIES AND LIMITATIONS (Journal of Contemporary Philology, 2018)
Comparative mythology is defined as systematic comparison of myths and mythic themes drawn from a wide variety of cultures and it served a variety of academic purposes. Starting from 19th century, scholars have examined the relationships between different myths to trace the development of religions and cultures. There were theorists who underline the linguistic relationships between myths, theorists who seek to reveal similar psychological forces behind the mythic stories or scientists who adopt the structuralist approach, looking for underlying structures shared by different myths. The phylogenetic line of study generally speculates that like genes, myths evolve by a process of descent with modification and the striking parallels between biological and mythological evolution  allows  the  use  of  computational  statistics  to  infer  evolutionary relatedness and to build the most likely phylogenetic trees. One of the most interesting new approaches to myth has been proposed by Michael Witzel who explains the cross-cultural similarities of myth in at least three ways other than common origin: human universals, independent invention and diffusion.
Keywords: myth; comparative mythology; mythic structures; approaches (linguistic, psychological, anthropological)